2022
DOI: 10.1007/s00520-022-07413-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a comprehensive medication review to improve medication use for patients with cancer and comorbid conditions

Abstract: Purpose A focus on oral medications for patients receiving care from both oncologists and primary care providers elicits an opportunity for improvement in patient outcomes. The purpose of this pilot study was to explore the feasibility and appropriateness of a comprehensive medication review (CMR) by a primary care pharmacist in a population of patients with cancer and chronic conditions. Methods Adult patients who received both cancer and primary care at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Third, this collaboration alongside oncologists/hematologists is probably feasible and efficient because patients with diabetes and cancer are patients with an elevated incidence of drug-related complications. They are often old with other comorbidities and an elevated number of medicines [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, this collaboration alongside oncologists/hematologists is probably feasible and efficient because patients with diabetes and cancer are patients with an elevated incidence of drug-related complications. They are often old with other comorbidities and an elevated number of medicines [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activity is not regulated uniformly among countries: for example, in the United Kingdom and the U.S.A., it is structured as a service within pharmaceutical care or by public pharmacies [16,17]; in some European countries, including Italy, it is freely organized at the regional level. MedRev can be a simple interview with the patient and the reconciliation of his or her personal drug therapy, or it can be structured with dedicated tools and algorithms [18]. A systematic review presenting various tools and methods in oncology is reported by Whitman et al [19].…”
Section: Introductionmentioning
confidence: 99%